Storytelling as an Experiential Marketing Strategy for Non-Alcoholic Beverages: Its Impact on Guest Engagement and Satisfaction at The Balcone Suites and Resort Bukittinggi - Melin Julianti; Lise Lise Asnur; Dede Muslihat (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study was motivated by the importance of creating a memorable guest experience as part of efforts to improve service quality in the hospitality industry. The study aims to analyze the effect of storytelling in the presentation of non-alcoholic beverages on guest engagement and satisfaction levels at The Balcone Suites and Resort Bukittinggi. The study employed a quantitative method with a causal-associative approach. Data were collected through a questionnaire distributed to 100 guests who had previously enjoyed non-alcoholic beverages at The Balcone Suites and Resort Bukittinggi. Data analysis was conducted using simple linear regression. The results indicate that storytelling in the serving of non-alcoholic beverages falls into the “very good” category, engagement levels fall into the “good” category, and guest satisfaction falls into the “very good” category. Furthermore, storytelling was found to have a positive and significant effect on engagement levels and guest satisfaction. These findings indicate that the application of storytelling in the serving of non-alcoholic beverages can create a more meaningful experience, increase guest engagement, and enhance their satisfaction with the services provided. Therefore, storytelling can be utilized as a service strategy to improve the quality of the guest experience in the hospitality industry.